Smartphone-based robot control for localisation - Nik Mahmod, Nik Firdaus (2015)
This project developed to use smartphone as a robot controller since it’s more powerful and equipped with several sensors that are useful for robots. The project uses Android application as well as Arduino microcontroller to locate and control the robot via DTMF tone from distance. Magnetometer and accelerometer sensor is used as input to trigger mobile robot movement for localisation purpose. The input sensor is designed to generate DTMF tone based on North Pole direction and force the robot to move only one direction referenced by North Pole. Several analyses have been done such as network provider analysis, robot operator analysis, sensor analysis as well as robot localisation analysis. The mobile robot was able to be controlled via developed Android application and all analyses regarding to robot performance is taken for future development purpose.